Polymyoclonus, laryngospasm, and cerebellar ataxia associated with adenocarcinoma and multiple neural cation channel autoantibodies - Lim, S.; Mason, W.P.; Young, N.P.; Chen, R.; Bower, J.H.; McKeon, A.; Pittock, S.J.; Lang, A.E. (American Medical Association, 2009)
OBJECTIVE: To describe and provide audiovisual documentation of a syndrome of polymyoclonus, laryngospasm, and cerebellar ataxia associated with adenocarcinoma and multiple neural cation channel autoantibodies.